2019
DOI: 10.1101/764522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA replication stress induced by trifluridine determines tumor cell fate according to p53 status

Abstract: words)DNA replication stress is a predominant cause of genome instability, a driver of tumorigenesis and malignant progression. Nucleoside analog-type chemotherapeutic drugs introduce DNA damage and exacerbate DNA replication stress in tumor cells. However, the mechanisms underlying tumor cytotoxicity triggered by the drugs are not fully understood.Here, we show that the fluorinated thymidine analog trifluridine (FTD), an active component of the chemotherapeutic drug trifluridine/tipiracil, delayed DNA synthes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 46 publications
(20 reference statements)
2
11
0
Order By: Relevance
“…Plasma concentrations of thymidine may affect FTD incorporation, because thymidine concentrations in culture media affect FTD incorporation into human cancer cell lines. 6,12 These variables may determine the percentage of FTDpositive PBMC during the early phase of FTD/TPI treatment and subsequently affect the occurrence of severe hematological adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of thymidine may affect FTD incorporation, because thymidine concentrations in culture media affect FTD incorporation into human cancer cell lines. 6,12 These variables may determine the percentage of FTDpositive PBMC during the early phase of FTD/TPI treatment and subsequently affect the occurrence of severe hematological adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 When FTD is incorporated into the DNA of tumor cells during DNA replication, it exerts antitumor activity 5 and induces DNA replication stress, which suppresses tumor growth irrespective of TP53 mutations. 6,7 Furthermore, the incorporation of FTD into proliferating normal cells may trigger adverse events. In a mouse model, FTD is efficiently incorporated into bone marrow cells, 8 which is associated with hematological toxicity caused by bone marrow suppression (eg, neutropenia or leukopenia), representing the most frequent adverse event of FTD/TPI.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of FTD-induced DNA replication stress, tumor cells expressing wild-type p53 exhibit p53-p21 pathway activation, cyclin B1 degradation during G2 phase, mitotic skipping, and subsequently cellular senescence. However, we have previously shown that mitotic entry, aberrant chromosome segregation, and apoptosis occurred in isogenic p53-null mutant cells (7).…”
Section: Introductionmentioning
confidence: 95%
“…The triphosphate is then incorporated into DNA strands during DNA replication. Incorporation of FTD into DNA induces retarded replication fork progression (termed DNA replication stress) and the associated cellular response to stress (7,8). Although FTD-induced, p53-status-independent growth suppression has 5 been reported (7,9), its effect was typically determined by different mechanisms in a p53-status-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation